2021
DOI: 10.3390/biology10101014
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Complex lncRNA/Pseudogene–miRNA–mRNA Crosstalk in Hormone-Dependent Cancers

Abstract: The discovery of microRNAs (miRNAs) has fundamentally transformed our understanding of gene regulation. The competing endogenous RNA (ceRNA) hypothesis postulates that messenger RNAs and other RNA transcripts, such as long non-coding RNAs and pseudogenes, can act as natural miRNA sponges. These RNAs influence each other’s expression levels by competing for the same pool of miRNAs through miRNA response elements on their target transcripts, thereby modulating gene expression and protein activity. In recent year… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The competing endogenous RNA (ceRNA) hypothesis is proposed as an essential post‐transcriptional regulation mechanism. LncRNA, pseudogene, mRNA, and other endogenous RNAs contain some identical miRNA binding sites, which can competitively bind common miRNAs to weaken their inhibition of target genes, thereby improving the expression level of target genes and regulating cell life activities 17 . This new hypothesis has gradually become a research hotspot and has been confirmed in various signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The competing endogenous RNA (ceRNA) hypothesis is proposed as an essential post‐transcriptional regulation mechanism. LncRNA, pseudogene, mRNA, and other endogenous RNAs contain some identical miRNA binding sites, which can competitively bind common miRNAs to weaken their inhibition of target genes, thereby improving the expression level of target genes and regulating cell life activities 17 . This new hypothesis has gradually become a research hotspot and has been confirmed in various signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous bioinformatic study identified shared ceRNAs (both lncRNAs and mRNAs) across PRAD, BRCA, COLCA and UCEC, considering miRNAs as the only gene regulator in the ceRNA network 6 . This study has integrated conventional ceRNA networks with DM, TF and CNA data using a machine‐learning approach, ‘Cancerin.’ According to our results, DM, TF and CNA significantly have cut‐off shared ceRNAs across HD cancers found from the conventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…We used three thresholds as follows: the hypergeometric test p < 0.05, the Pearson correlation coefficient of lncRNA–mRNA or mRNA–mRNA pairs > 0.40, and the adjusted p of mscor < 0.05 to infer ceRNA candidates of each HD cancer. We have extensively described these methods in our previous conventional ceRNA network analyses paper 6 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations